Simplifikasi Ahli Waris Testamentair atas Pembagian Harta Warisan Terhadap Janda - Kairuddin Karim (Jurnal Litigasi Amsir, 2022)
This study aims to determine the distribution of inheritance for widows according to the Criminal Code/B.W. and to find out the influence of the heirs of the will on the distribution of inheritance to the widows. The research method used is normative legal research. The results showed the influence of the heirs of the will on the distribution of inheritance to the widow in the inheritance of the will, the position of the widow (wife) is not the same as the position of the child, this is because the child has his own absolute right. the share while the widow (wife) does not have an absolute share of her own, the absolute share is called legitimie portie, related to the share obtained by the widow (wife) lies in the number of wills left by the heirs, the greater the number. of the will, the widow (wife) will receive less or nothing, but if the number of wills is small, the widow (wife) can have a share of the rest of the inheritance.